2021
DOI: 10.1021/acs.jafc.1c06280
|View full text |Cite
|
Sign up to set email alerts
|

trans 10, cis 12, but Not cis 9, trans 11 Conjugated Linoleic Acid Isomer Enhances Exercise Endurance by Increasing Oxidative Skeletal Muscle Fiber Type via Toll-like Receptor 4 Signaling in Mice

Abstract: Conjugated linoleic acid (CLA) has been implicated in regulating muscle fiber. However, which isomer elicits this effect and the underlying mechanisms remain unclear. Here, male C57BL6/J mice and C2C12 cells were treated with two CLA isomers, and the exercise endurance, skeletal muscle fiber type, and involvement of Toll-like receptor 4 (TLR4) signaling were assessed. The results demonstrated that dietary t10, c12, but not c9, t11-CLA isomer enhanced exercise endurance of mice (from 115.88 ± 11.21 to 130.00 ± … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…23 Previous studies also found that CLA could change the muscle fiber type transformation and promote the formation of an oxidative muscle fiber type in mice and in C2C12 myotubes. 24,25 In addition, we also found that CLA could decrease the content of capric acid (C10:0) in the LDM. Capric acid has been reported to increase the capacity for fatty acid oxidation in skeletal muscle.…”
Section: Discussionmentioning
confidence: 54%
“…23 Previous studies also found that CLA could change the muscle fiber type transformation and promote the formation of an oxidative muscle fiber type in mice and in C2C12 myotubes. 24,25 In addition, we also found that CLA could decrease the content of capric acid (C10:0) in the LDM. Capric acid has been reported to increase the capacity for fatty acid oxidation in skeletal muscle.…”
Section: Discussionmentioning
confidence: 54%
“…48 Additionally, our published results demonstrated that t10, c12-CLA, but not c9, t11-CLA enhanced exercise endurance by increasing the oxidative skeletal muscle fiber type in mice. 49 Similarly, 50 μM c9, t11-CLA increased the expression of UCP1 in human precursor adipocytes, while t10, c12-CLA inhibited the expression of UCP1 in human precursor adipocytes after 12 h treatment. 50 The specific reasons why different CLA isomers have different regulatory effects are not clear, but the possible reasons may be the differences in the CLA treatment concentration, experimental duration and cell model.…”
Section: Discussionmentioning
confidence: 90%
“…48 Additionally, our published results demonstrated that t10, c12-CLA, but not c9, t11-CLA enhanced exercise endurance by increasing the oxidative skeletal muscle fiber type in mice. 49 Similarly, 50 μM c9, t11-CLA increased the expression of UCP1…”
Section: Discussionmentioning
confidence: 94%
“…Duan, Chen said that Conjugated linoleic acid is related to the regulation of muscle fibers. He pointed out through experiments that Conjugated linoleic acid isomers increase the type of oxidized skeletal muscle fibers through toll like receptor 4 signals to enhance exercise endurance ( Duan et al, 2021 ). Scholars’ research on conjugated materials and muscles can provide some theoretical support for this article, but due to the lack of emphasis on the application of conjugated materials in muscle motion recovery, the research does not have much reference value.…”
Section: Introductionmentioning
confidence: 99%